Relationship between Incisive Papilla and Maxillary Central Incisors in Complete Dentures and Dentate People - Kosar Dadgar; Atefeh Ramezani; Jamshid Yazdani Charati; Soheila Hasani; Aliakbar Estebsari (Journal of Mazandaran University of Medical Sciences, 2022)
Background and purpose: This study was carried out to determine the relationship between maxillary central incisors and incisive papilla in complete dentures and compare that with dentate people. Materials and methods: In this descriptive-analytical study, the horizontal distance between the maximum prominence of labial surface of maxillary central incisors to the middle and posterior points of incisor papilla was measured using a caliper, on the casts prepared from 30 dentate patients and 30 complete dentures made in Dental School affiliated with Mazandaran University of Medical Sciences. Results: Average distance between the midpoint of incisive papilla to the labial surface was 9.641±0.866 mm in dentate people and 8.851±1.504 mm in complete dentures. The mean distance between the posterior point of incisive papilla and the labial surface was 12.815±1.264 mm in dentate people and 10.788±1.837 mm in complete dentures. Independent t-test showed significant difference between the two groups in mean distance between the midpoint and the labial surface (0.790 mm, P<0.05). The distance between the posterior point and the labial surface was also found to be significantly different between the two groups (2.026±0.407 mm, P<0.001). Conclusion: According to the limitations of this study, the midpoint of incisive papilla is suggested to be more reliable than posterior point in assessing the position of anterior maxillary teeth among complete denture patients.